PERHITUNGAN BEBAN KERJA OPERATOR LINI PERAKITAN KOMPRESOR TIPE SVC93E20PBE UNIT REFRIGERATOR R600A DI PT. PANASONIC MANUFACTURING INDONESIA: Optimizing Operator Workload for SVC93E20PBE Compressor Type Assembly Line in Refrigerator Unit R600A at PT. Panasonic Manufacturing Indonesia - Anggraini, Meli; Azisah, Nur Aini; Nugraha, Diki; Medikano, Alsen (Universitas Negeri Jakarta, 2024)
Panasonic Manufacturing Indonesia produces electronic equipment especially for the needs of ordinary consumers, business and industry such as refrigerators, ACs, water pumps, fans, washing machines and audio with problems with refrigerator and AC production units. The research was carried out on the SVC93E20PBE type compressor assembly line for the R600A refrigerator unit with the problem of operator workload being too high, above 100%. The research was conducted for 30 days on three compressor assembly line operators using the workload analysis method, with the aim of obtaining the productive percentage and workload level of operators on the SVC93E20PBE type compressor assembly line for the R600A refrigerator unit. Data was taken following a standard work sampling observation sheet, containing employee activities while working or unemployed with adjustments. The results of workload measurement using the workload analysis method showed that operator 1's workload was 133.63%, operator 2's workload was 133.62%, and operator 3's workload was 133.74%. Based on the description of the workload results for compressor assembly operators for the SVC93E20PBE type 600A refrigerator unit, the researcher proposes the addition of two operators to the compressor assembly line, a total of five operators with a workload for each operator of 80.198%.